2021
DOI: 10.5194/acp-2021-385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of emission changes in China from 2010 to 2017 on domestic and intercontinental air quality and health effect

Abstract: Abstract. China has seen dramatic emission changes from 2010, especially after the implementation of Clean Air Action in 2013, with significant air quality and human health benefits observed. Air pollutants, such as PM2.5 and surface ozone, as well as their precursors, have long enough lifetime in the troposphere which can be easily transported downwind. So emission changes in China will not only change the regional air quality domestically, but also affect the air quality in downwind regions. In this study, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, found the modeled spatial variability of nitrogen dioxides (NO2) matches well with surface observations but with a large bias in their concentrations. Zhang et al (2021) exhibited a difference between modeled and observed surface fine particulate matter (PM2.5) and ozone (O3): the modeled PM2.5 and O3 concentrations are higher than observations by about 40% and 15% in China in 2013-2017, respectively. Based on CTMs, data assimilation techniques integrate simulations and observations and thus can improve the modeled atmospheric compositions. For instance, Feng et al (2018) found the assimilation of surface PM2.5 observations can effectively reduce the uncertainties in PM2.5 forecasts.…”
Section: Introductionmentioning
confidence: 92%
“…For example, found the modeled spatial variability of nitrogen dioxides (NO2) matches well with surface observations but with a large bias in their concentrations. Zhang et al (2021) exhibited a difference between modeled and observed surface fine particulate matter (PM2.5) and ozone (O3): the modeled PM2.5 and O3 concentrations are higher than observations by about 40% and 15% in China in 2013-2017, respectively. Based on CTMs, data assimilation techniques integrate simulations and observations and thus can improve the modeled atmospheric compositions. For instance, Feng et al (2018) found the assimilation of surface PM2.5 observations can effectively reduce the uncertainties in PM2.5 forecasts.…”
Section: Introductionmentioning
confidence: 92%
“…Since 2013, elevated ambient levels of particulate matter over China have been largely alleviated by effective emission controls (Zhang et al., 2021). However, an opposite trend has been observed in the concentrations of surface ozone over China, which have rapidly increased (Li et al., 2019; Lu, Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%